2013
DOI: 10.1024/1662-9647/a000096
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Inconsistency and Practice-Related Learning in Older Adults

Abstract: The current study examined predictors of individual differences in the magnitude of practice-related improvements achieved by 87 older adults (meanage 63.52 years) over 18-weeks of cognitive practice. Cognitive inconsistency in both baseline trial-to-trial reaction times and week-to-week accuracy scores was included as predictors of practice-related gains in two measures of processing speed. Conditional growth models revealed that both reaction time and accuracy level and rate-of-change in functioning were rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
(117 reference statements)
1
2
0
Order By: Relevance
“…Consistent with previous research (Dzierzewski et al, 2013; Hultsch et al, 2002), we observed large fluctuations in global cognitive functioning (i.e., 22% of the total variance in cognitive functioning) in a group of older adults under long-term treatment for depression. We also replicated previous findings of increased age and lower educational attainment being related to lower global cognitive functioning (Plassman et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous research (Dzierzewski et al, 2013; Hultsch et al, 2002), we observed large fluctuations in global cognitive functioning (i.e., 22% of the total variance in cognitive functioning) in a group of older adults under long-term treatment for depression. We also replicated previous findings of increased age and lower educational attainment being related to lower global cognitive functioning (Plassman et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Such clinical data have fueled empirical investigations into the relationships between late-life depressive symptoms and cognitive functioning; however, these investigations have not produced consistent results (e.g., Dotson et al, 2008; Han et al, 2006). Potential explanations for the disparate results include investigation of these relationships in non-clinical samples of older adults and the fluctuating course of both late-life cognitive functioning (Dzierzewski et al, 2013; Hultsch et al, 2002) and late-life depression (Beekman et al, 2002; Dautovich et al, 2014). The present investigation sought to investigate the relationships between depressive symptoms and cognitive functioning across the treatment history of late-life major depressive disorder (MDD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation